Skills in European entrepreneurial finance: A survey-based analysis of skills and skills gaps in the VC and PE markets - Helmut Krämer-Eis; Antonia Botsari; Frank Lang; Clarissa Hahn (European Investment Fund (EIF), 2024)
Based on the EIF VC and PE Mid-Market Surveys (the largest of its kind in Europe), whereby 671 fund managers investing in either the VC or the PE Mid-Market in Europe provided their opinions and input, our new research report delves deeper into skills and skills gaps in the European ecosystem, at both investor and portfolio company level. Key findings: While the importance attributed to specific skills differs among VC and PE mid-market fund managers, a common concern is that sustainability-related knowledge and STEM skills are currently missing at investor level. Training is the main means to fill soft-skills gaps, while new hiring or outsourcing is used to fill gaps arising from industry knowledge, legal and STEM skills. Team culture fit and personality are the most important qualities when hiring junior talent. For senior recruits, network and work experience are also important. Fund managers build their teams according to the importance they assign to the different skills, perceiving as relatively more important the skills they are endowed with in their own investment teams. By contrast, at portfolio company level, they tend to assign higher importance to the skills missing in the management team of their portfolio companies. An investee's management team is the most important investment selection criterion stated by fund managers. At the same time, both VC and PE mid-market fund managers perceive leadership and people management as the most important skill for the management team of their portfolio companies, but also the one lacking the most. The skills of investor and portfolio company teams can to a certain extent complement each other. Hence, jointly analysing skills gaps at both the investor and the portfolio company level enables us to identify, on the one hand, skills for which portfolio companies need to be on average autonomous or self-sustaining, and on the other hand, skills in which fund managers can support and provide value-added to portfolio companies.
Keywords: 330